Quality Management Analysis of Tertiary Institution Operational Performance in Implementing Blended Learning in New Normal Era for Students Introduction to Business Subject - Dewi Martha; Gusnafitri; Rusyaidi Thahery (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to find out how the operational performance and quality management of the tertiary institution is in implementing blended learning in the new normal era for students in introduction business subject particularly. In this research, the authors used a qualitative descriptive approach, focusing on the study of quality management through operational performance. The data collection techniques applied in this research are observation, interview, and documentation. The results of this research state that operational performance of tertiary institutions in implementing blended learning in the new normal era for students in introduction to business subject has a great responsibility in improving the quality of the blended learning system on an ongoing basis